Low-Glycemic-Index/Load Desserts Decrease Glycemic and Insulinemic Response in Patients with Type 2 Diabetes Mellitus - Argiana, Vasiliki (Nutrients, 2020)
Diabetes mellitus is a chronic disease whose prevalence is growing worldwide. Consumption of desserts with low glycemic index (GI) and low glycemic load (GL) in a balanced hypocaloric diet has a positive impact on anthropometric and metabolic parameters in patients with type 2 diabetes mellitus (T2DM). The aim of the present study was to evaluate the glycemic and insulinemic response after consumption of desserts with low GI/GL in patients with T2DM. Fifty-one patients consumed either 83 g of the conventional dessert or 150 g of the low GI/GL dessert in random order after an overnight fast. Serum glucose, triglycerides, and insulin were measured at baseline (immediately before ingestion) and at 30, 60, 90, and 120 min postprandially. Subjective appetite measurements were performed using visual analog scales (VASs). There were significant differences at 30 (p = 0.014), 60 (p < 0.001), and 90 min (p < 0.001) postprandially between the two desserts for glucose and at 30 (p = 0.014) and 60 min (p = 0.033) postprandially for insulin. Glucose iAUC was significantly lower in low-GI/GL dessert compared to control (p < 0.001). Serum triglycerides and insulin iAUC did not differ between the two trials. Fullness VAS ratings were significantly higher after consumption of the low-GI/GL dessert compared to conventional dessert. Likewise, hunger, additional food, and additional food quantity VAS ratings were significantly lower after the consumption of the low-GI/GL dessert compared to control. Consumption of low-GI/GL dessert indicates a positive impact on metabolic parameters in T2DM patients.